1997
DOI: 10.1002/(sici)1097-4547(19971015)50:2<248::aid-jnr13>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

CNP2 mRNA directs synthesis of both CNP1 and CNP2 polypeptides

Abstract: The ribosome scanning model for translational initiation predicts that eukaryotic mRNAs should, as a rule, be monocistronic. However, cases have recently been described of eukaryotic mRNAs producing more than one protein through alternative translational initiation at several different AUG codons. The present work reports the occurrence of two translational start sites on the mRNA encoding isoform 2 of the myelin marker enzyme 2',3'-cyclic nucleotide 3'-phosphodiesterase (CNP) in rat and mouse. We show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Several studies have shown a specific expression of CNP during differentiation of oligodendrocytes (Scherer et al, 1994;Yuan et al, 2002) and it has been proven to faithfully direct expression of a transgene to OPCs and differentiated oligodendrocytes (Gravel et al, 1998;Chandross et al, 1999;Yuan et al, 2002). The Cnp promoter consists of two separate promoter regions resulting in two isoforms, Cnp1 (46 kDa) and Cnp2 (48 kDa), encoded by the same gene (O'Neill et al, 1997). The proximal promoter, which regulates transcription of Cnp1 mRNA, contains one open-reading frame for CNP1 protein and is mainly active after birth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown a specific expression of CNP during differentiation of oligodendrocytes (Scherer et al, 1994;Yuan et al, 2002) and it has been proven to faithfully direct expression of a transgene to OPCs and differentiated oligodendrocytes (Gravel et al, 1998;Chandross et al, 1999;Yuan et al, 2002). The Cnp promoter consists of two separate promoter regions resulting in two isoforms, Cnp1 (46 kDa) and Cnp2 (48 kDa), encoded by the same gene (O'Neill et al, 1997). The proximal promoter, which regulates transcription of Cnp1 mRNA, contains one open-reading frame for CNP1 protein and is mainly active after birth.…”
Section: Resultsmentioning
confidence: 99%
“…The proximal promoter, which regulates transcription of Cnp1 mRNA, contains one open-reading frame for CNP1 protein and is mainly active after birth. The distal promoter regulates transcription of Cnp2 mRNA, which produces both CNP1 and CNP2 polypeptides and is active both in embryonic brain and postnatally (O'Neill et al, 1997). The transgenic construct contained the entire mouse Cnp promoter region coupled to the Tv-a gene followed by an ires (internal ribosomal entry site) sequence and the lacZ gene ( Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Two CNP isoforms, CNP1 (46 kDa) and CNP2 (48 kDa), were found (16,23) that are encoded by a single gene. The two isoforms are due to the presence of two alternative translation start sites (28). Several posttranslational modifications of CNP, such as phosphorylation, isoprenylation, and acylation, with unclear functional consequences are known (1,2,10,36,38,39).…”
mentioning
confidence: 99%
“…The CNP is a protein of unknown function that is abundantly expressed in myelinating cells (Scherer et al, 1994;O'Neill et al, 1997). The CNP is also expressed at low level in both neuronal and nonneuronal tissues as described in Introduction.…”
Section: Discussionmentioning
confidence: 99%
“…The 2',3'-cyclic nucleotide 3'-phosphodiesterase (CNP; EC 3.1.4.37) is expressed as two isoforms with an apparent molecular mass of 46 kDa (CNP1) and 48 kDa (CNP2), which are produced by alternative ribosomal initiation at two different AUG codons, thus differing each other only by the 20-amino acid extension at the N terminus (O'Neill et al, 1997). Despite its lengthy history, relatively little is known about the function of CNP.…”
Section: Introductionmentioning
confidence: 97%